Developments in flood maps for flood risk management in Scotland. (3rd April 2019) - McLaughlin, Mark
ABSTRACT: Sustainable flood risk management in Scotland is underpinned by the Flood Risk Management (Scotland) Act 2009. Effective delivery of actions to reduce the adverse impact of flooding are dependent on a collaborative approach by Responsible Authorities and a common understanding of flood hazard and risk. Over the last few decades, flood hazard maps have established a prominent role as essential tools in supporting effective flood risk management. They have developed as a result of improved national datasets and advances in computer processing. Improvements in modelling confidence and in the spatial representation of hazard and risk-inform confident actions set out in Flood Risk Management Strategies that coordinate actions supporting adaptation to future hazard conditions. The continued development of the accurate spatial representation of flood hazard and risk is an essential component of enhancing resilience in the face of future climate change.